Understanding the influence of filler type and asphalt binder content on the moisture and fatigue resistance of asphalt mortars - R. Tauste; A.E. Hidalgo; G.M. García; F. Moreno-Navarro; M.C. Rubio-Gámez (Materiales de Construccion, 2022)
An adequate moisture resistance is a key element to guarantee the durability of asphalt materials. This paper identifies the influence of filler typology and bitumen content on the mechanical response of asphalt mortars before and after water action. Two fillers were evaluated: Portland cement and Calcium carbonate, along with different contents of a penetration bitumen (B35/50). Stiffness, ductility, and fatigue were evaluated through a new protocol for asphalt mortar samples using a 3-point-bending test on DMA (Dynamic Mechanical Analyzer). The use of Portland cement presents higher stiffness, lower ductility, and improved fatigue and water resistance compared to Calcium carbonate. It is also possible to optimize bitumen content based on fatigue results. Content beyond the optimal reduce variations after water action but compromise fatigue resistance. Lower content leads to a poorer performance in both terms. This methodology enables asphalt mortar characterisation as a tool to optimise the design of asphalt materials.